Podstawy organizacji Zakładu Naukowego Fundacji Wiktora hr. Baworowskiego w Tarnopolu: lokalizacja – budynek – personel - Gwioździk, Joalnta (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
Count Wiktor Baworowski planned to establish a Research Institute in Tarnopol to serve as an educational institution for the community of the south-eastern borderlands of the Republic of Poland. Therefore, the Executive Council undertook to organise a library and a museum in Tarnopol to aid popular science, self-education and popularisation of Polish culture among local residents. This article analyses the undertaken organisational work. An important stage was the selection of the library building; Baworowski left detailed plans for its construction and equipment. Finally, a decision was made to adapt the rooms of the so-called new castle in Tarnopol. The staff of the facility was also carefully selected: the library was organised by Tadeusz Landenberger, while Leon Popiel became the manager of the library and the museum. The Institute was supervised by the director of the Baworovianum in Lvov - Rudolf Kotula.